Cellular stress modulates severity of the inflammatory response in lungs via cell surface BiP - Rico-Llanos, Gustavo; Porras-Perales, Óscar; Escalante, Sandra; Vázquez-Calero, Daniel B.; Valiente, Lucía; Castillo, María I.; Pérez-Tejeiro, José Miguel; Baglietto-Vargas, David; Becerra, José; Reguera, José María; Duran, Ivan; Csukasi, Fabiana (Frontiers in Immunology, 2022)
Inflammation is a central pathogenic feature of the acute respiratory distress syndrome (ARDS) in COVID-19. Previous pathologies such as diabetes, autoimmune or cardiovascular diseases become risk factors for the severe hyperinflammatory syndrome. A common feature among these risk factors is the subclinical presence of cellular stress, a finding that has gained attention after the discovery that BiP (GRP78), a master regulator of stress, participates in the SARS-CoV-2 recognition. Here, we show that BiP serum levels are higher in COVID-19 patients who present certain risk factors. Moreover, early during the infection, BiP levels predict severe pneumonia, supporting the use of BiP as a prognosis biomarker. Using a mouse model of pulmonary inflammation, we demonstrate that cell surface BiP (cs-BiP) responds by increasing its levels in leukocytes. Neutrophiles show the highest levels of cs-BiP and respond by increasing their population, whereas alveolar macrophages increase their levels of cs-BiP. The modulation of cellular stress with the use of a clinically approved drug, 4-PBA, resulted in the amelioration of the lung hyperinflammatory response, supporting the anti-stress therapy as a valid therapeutic strategy for patients developing ARDS. Finally, we identified stress-modulated proteins that shed light into the mechanism underlying the cellular stress-inflammation network in lungs.